Platelet-lymphocyte ratio and sepsis outcome in children - Ferry Kurniawan; Jeanette I. Ch. Manoppo; Ari Lukas Runtunuwu; Novie Homenta Rampengan; Julius Lolombulan (Indonesian Pediatric Society, 2021)
Background Sepsis is the most common cause of death in infants and children worldwide. Identification of patients with a high risk of death and accurately anticipating outcomes in the early phase is very important in order to provide adequate intervention to the patient. Predictors and scoring systems have been used to determine the prognosis of sepsis n children. The platelet-lymphocyte ratio (PLR), a newly-used marker for inflammation, has received recent attention, as it can act as an indicator in a variety of diseases, including sepsis. Objective o investigate the relationship between PLR and clinical outcomes in pediatric patients with sepsis. Methods This study was conducted using an analytic, observational method with a prospective cohort approach in children with sepsis in the Pediatric Intensive Care Unit (PICU) of Prof. Dr. R. D. Kandou Central General Hospital, Manado, North Sulawesi, from February to August 2020. We analyzed patients’ platelet-lymphocyteratio (PLR), mortality rate, and length of stay using SPSS software. The PLR were recorded once within the first 24 hours of PICU admission. Results Of 96 PICU patients, 87 patients were eligible for this study. In total, 50 patients (57.47%) died. Mean PLR was 77.53 among sepsis survivors and 157.2 among non-survivors (rpb=0.566, P<0.0001) indicating a strong relationship between PLR and mortality. We also found a strong positive linear relationship between PLR and PICU length of stay. Conclusion Platelet-lymphocyte ratio is a predictor of sepsis outcomes that can be easily and inexpensively checked. Thus, it can be used in regions with limited health facilities.